First data on box-tree moth seasonal development in the green areas in Zhytomyr - Андреєва, О. Ю.; Мартинчук, І. В.; Іванюк, Т. М.; Матковська, С. І.; Марчук, Д. О. (Forestry and Forest Melioration, 2024)
Introduction Box-tree moth Cydalima perspectalis (Walker, 1859) (Lepidoptera: Crambidae) originates from east Asia. This pest was revealed in Europe in 2006 and is now present in most of the regions of Ukraine. In its range, the box-tree moth can develop in two to five generations per year, causing the weakening and mortality of Buxus L., particularly Buxus sempervirens L. The analysis of publications shows the variation in the timing of box-tree moth development and the number of generations. Thus, in some regions of Asia, the pest has up to five generations, in the south of Romania – three, in Switzerland and Canada – two. The development of individual generations often overlaps, and it is difficult to determine their exact number. Some data on the duration of individual stages at a constant temperature were obtained during laboratory rearing of the box-tree moth and used for modeling its development and spread. We started detailed studies of this pest in Zhytomyr in the spring of 2022, when more than 10 % of boxwood bushes were inhabited, and the density of caterpillars was from 7 to 20 specimens per bush. This research aimed to identify the features of box-tree moth seasonal development in the green areas of Zhytomyr to determine the optimal terms for monitoring the spread and development of this pest and measures for its control. Materials and Methods Our research was carried out in the Botanical Garden of the Polissky National University (Zhytomyr, 50°15?09? N; 28°42?00? E). The phenology of the box-tree moth was studied during 2022, 2023 and the first half of 2024 by inspecting box-tree plants with an interval of two weeks before the beginning of the growing season and with an interval of one week during the growing season. On each date, the stages of the pest were assessed by examining box-tree branches (10 branches 10 cm long on each of the 10 model plants). In particular, the dates of caterpillars’ hibernation, the beginning feeding after wintering, their pupation, moths swarming, eggs, caterpillars, and pupae in the next generations were recorded. The caterpillars’ instar was estimated by head capsule width. Data from the Zhytomyr weather station were used to calculate the average air temperature for a month and during the individual stages of the box-tree moth in 2022–2024. Results and Conclusions The box-tree moth develops in two complete generations in the Botanical Garden of the Polissky National University. Caterpillars of the third generation, starting from September, slow down their development and enter diapause in the 3rd–4th instars. The end of the first period of the imago swarming (from the third decade of June to the third decade of July) is close to the beginning of the second period of the imago swarming (from the first decade of August to the first decade of September). The possibility of overlapping development of individuals of two generations indicates the threat of new box-tree plants being populated and damaged during most of the summer. The termination of caterpillar diapause and resumption of feeding in the spring occurs approximately after the date of a stable temperature transition over 10 °C. Inspection of box plants and their protection, if necessary, must be carried out at this time. The obtained data on the box-tree moth seasonal development in its secondary range are of theoretical importance for clarifying the trends in the seasonal cycles of multivoltine phytophagous insects under climate change. 5 Figs., 23 Refs.